2016
DOI: 10.1186/s40712-016-0064-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of load capacity of gears with an asymmetric tooth profile

Abstract: Background: An ISO standard tooth profile has a symmetric pressure angle of 20°. However, the load capacity can be increased with respect to bending and contact pressure by increasing the pressure angle on the meshing side of an asymmetric tooth. Accordingly, we analyzed the torque transmission capacity of asymmetric gears with various pressure angles. Methods: We calculated the deflection and bending stress of teeth by the finite element method and found the root stress taking into account the load-sharing ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Coefficient of friction measurements were carried out with a force of 30 N. In the contact area between the ball and the plate there is a maximum Hertzian pressure of pH = 947.8 N/mm 2 . This contact pressure of the MTM specimen is equivalent to the maximum Hertzian contact stress of a loaded gear pair with approximately FN = 1000 N in the LPSTC and HPSTC zone along the line of action [16]. The oil to be examined was heated to 80 °C in all measurement series.…”
Section: Coefficient Of Friction Measurement Resultsmentioning
confidence: 99%
“…Coefficient of friction measurements were carried out with a force of 30 N. In the contact area between the ball and the plate there is a maximum Hertzian pressure of pH = 947.8 N/mm 2 . This contact pressure of the MTM specimen is equivalent to the maximum Hertzian contact stress of a loaded gear pair with approximately FN = 1000 N in the LPSTC and HPSTC zone along the line of action [16]. The oil to be examined was heated to 80 °C in all measurement series.…”
Section: Coefficient Of Friction Measurement Resultsmentioning
confidence: 99%
“…In addition to material factors, there is also a production process, especially dimensional accuracy. Changes in the dimensions of the tooth flank are very high, which will affect to the tooth contact point to become out of focus, so wear resistance decreases, this is explained by M. Ristivojević et al [18] that Uniformity and intensity of tooth flank wear depend on pitch point position on the profiles of meshed teeth and will be very critical at maximum torque capacity [85].…”
Section: Addendum Circle Diametermentioning
confidence: 99%
“…In the same year, Miyazaki et al. 24 took into account the load distribution ratio, calculated the deflection and bending stress of the gear by the finite element method and studied the torque transmission capacity of the asymmetric gear with different pressure angles; In 2017, Zhou C. J et al. 25 showed that the effect of friction on bending strength of spiral bevel gears was greater than that of contact strength, which was verified by theoretical calculation and finite element analysis.…”
Section: Introductionmentioning
confidence: 97%